Sistema de colaboración remota para equipos que gestionan procesos de innovación. (2019)
Purpose - The purpose of this project was to improve the experience of the teams that manage innovation within organizations, whether companies or educational institutions. Today the experience depends on having experts that facilitate the process, of having access to spaces specially equipped for collaboration that are known as innovation laboratories (i-labs), of having knowledge of tools that guide the collection and analysis processes of the information, and of the use of consumables of short useful life (post-its and markers). That is why we explored the benefits that digital tools and virtual representation of reality can bring to increase access to these limited spaces, guide the process of managing these projects, reduce waste of materials and increase the traceability of the information . Design /methodology / approach - The applied methodology for the development of this project was based on the double diamond process proposed by the "Design Council". The 4 stages of development (Discover, Define, Develop and Deliver) were transited to achieve the results. In-depth interviews were conducted with 10 innovation process facilitators to identify the most common barriers they face. Observations and empathy processes with students of masters focused on innovation were conducted to identify the difficulties that teams have to collaborate in the i-labs and outside them. Usability validation surveys of the proposal were carried out with people associated with teams and innovation areas of Cali and Colombian companies. These elements informed the iterative ideation and prototyping that was carried out in later stages.